Excited‐State Symmetry Breaking in an Aza‐Nanographene Dye. Issue 61 (2nd October 2019) - Bardi, Brunella; Krzeszewski, Maciej; Gryko, Daniel T.; Painelli, Anna; Terenziani, Francesca
Abstract: The photophysics of a structurally unique aza‐analogue of polycyclic aromatic hydrocarbons characterized by 12 conjugated rings and a curved architecture was studied in detail. The combined experimental and computational investigation reveals that the lowest excited state has charge‐transfer character, in spite of the absence of any peripheral electron‐withdrawing groups. The exceptionally electron‐rich core comprised of two fused pyrrole rings is responsible for it. The observed strong solvatofluorochromism is related to symmetry breaking occurring in the emitting excited state, leading to a significant dipole moment (13.5 D) in the relaxed excited state. The anomalously small fluorescence anisotropy of this molecule, which is qualitatively different from what is observed in standard quadrupolar dyes, is explained as due to the presence of excited states that are close in energy but have different polarization directions. Abstract : The emission solvatochromism of a centrosymmetric double helical π‐expanded pyrrolo[3, 2‐ b ]pyrrole is related to symmetry breaking of the first excited state. Strong emission from the charge‐transfer state is interpreted as borrowing intensity from the close‐lying localized transitions, thus explaining the high and stable fluorescence quantum yield.